Environmental exposure to asbestos: from geology to mesothelioma - Bayram, MEHMET; BAYRAM, MEHMET; Bakan, Nur Dilek (My University, 2014)
Purpose of reviewThis article aims to review the geological background of environmental asbestos exposure and the distribution of asbestos-related disease (ARD) in association with naturally occurring asbestos (NOA), and discusses the potential health risks associated with exposure to non-occupational asbestos.Recent findingsWith the motion of continental and oceanic plates, in some parts of the world serpentinites in the lower layer of the oceanic plate move into the continental plate and form the so-called ophiolites. Ophiolites consist of soil and rocks containing serpentine-type asbestos. There is an increase in ARDs in regions close to ophiolites. Indoor exposure and outdoor exposure to NOA, outdoor exposure to industrial asbestos and mines, urbanization and construction works in NOA regions are the known sources and types of environmental asbestos exposure.SummaryAlthough there is an expectance of decline in ARDs caused by industrial exposure to asbestos, the environmental exposure to asbestos is still a challenge waiting to be overcome.